O enquadramento do Bóia-Fria no ordenamento pátrio: a busca da classificação como segurado da Previdencia Social - Washington, Aroldo José (2014)
This work will be examined in the light of the Theory of Legal Argumentation , the weighting of constitutional principles relating to the Social Security Law . The goal will be to demonstrate that the rural worker flywheel , also called " float - cold ," Social Security is insured , and will seek classification as held Social Security therefore has the worker entitled to Social Security , despite there is no express legal provision , because it does not fit the definition of employee in the definition given by the Labor Law , as it is possible worker . In everyday practice , the employee steering wheel does not collect social security contributions , and consequently face this fact would not be insured framed as Social Security . Will demonstrate that this task is the assignment of borrower services , and therefore fits the employee steering wheel, as insured , with foundations of constitutional principles and rules governing the matter in understanding complied with the administrative and judicial . The research method is worked in a descriptive way , and will be developed with the research of labor and social security doctrines , organized with dogmatic and even search the Jurisprudence of the Courts dealing with this matter, which will bring clarity to the legal loophole which governs the matter